Do tacho ao bistrô: turismo, território e ressignificações culinárias no brejo paraibano - Sales, Josélio dos Santos (2025)
As a complex and dynamic activity, tourism involves socioeconomic, sociocultural and environmental implications, playing an important role in the territorial reconfiguration and cultural transformation of the territories where it occurs. In Brazil, the launch of the Tourism Regionalization Program (PRT) in 2004 (Brazil, 2005) encouraged the organization of Brazilian municipalities around tourism as a local development strategy, decentralizing tourism policy and strengthening the articulation between the national and regional spheres with a focus on valuing the territorial and local potential, including tangible and intangible cultural heritage. With the support of the Ministry of Tourism and the State Tourism Secretariats, tourist circuits were organized and adapted to regional specificities, promoting and integrating municipal tourism products and services. Thus, in 2006, Caminhos do Frio was launched. It connected the cities of the Brejo region of Paraíba. This included Bananeiras, which consolidated itself as a tourist destination. This was also supported by municipal tax exemptions that favored real estate developments focused on leisure and tourism, especially horizontal condominiums. This thesis analyzes how, in this context, the forms of food production and consumption in Bananeiras were transformed, both in its “regional/local” culinary expression and by the emergence of differentiated restaurants that appeared in that municipality from 2010 onwards. The methodology adopted included participant observation in fairs, bars, restaurants and local festivities, in addition to 29 interviews with former municipal managers, former secretaries of Culture and Tourism, merchants, local cooks, chefs, public and private agents, members of the Brejo Paraíba Tourism Forum and local residents, all impacted by the phenomena of Caminhos do Frio and horizontal condominiums. The data was collected throughout the years 2023 and 2024, with supplementary collections being carried out to complement the information. The research highlights how these events transformed the cultural, economic and gastronomic dynamics of Bananeiras, contributing to the construction of a new local identity, impacting the entire region of Brejo Paraibano. Although the theme presents itself as part of a dynamic tourism project, it involves the municipal and state political-economic fields and is constantly being reconfigured.